Effect of extrusion ratio on paraffinic mineral oil lubricant in cold forward extrusion - S. M., Hafis (2011)
A finite element (FE) analysis is made for steady-state two-dimensional forward extrusion with three different extrusion ratio values. Predicting extrusion force of aluminum billet extruded with palm oil lubricant will definitely be helpful in deciding the right extrusion ratio. Hence, the finite element method was applied to investigate the influence of extrusion ratio on palm oil lubricant. The extrusion ratios evaluated were 1.5, 2, and 3. The reference of the study was in accordance to the experiment results of 0.1 mg paraffinic mineral oil grade 95 (Pr95) with kinematic viscosity of 90.12 mm(2)/s at 40 degrees C for the extrusion ratio of 3. The result was found to be reliable once the FE model was validated by the established work. The extrusion force for each extrusion ratio was described and evaluated. The FE analysis also accounts for plasticity material flow and equivalent plastic strains in the deformation region. The analysis agreed that the extrusion ratio of 1.5 reduced the extrusion force compared to the extrusion ratio of 2 and 3. This was confirmed by the plotted equivalent plastic strain deformation which shows that the high value of equivalent plastic strain near the extrusion die surface was decreased. As a result, the extrusion force becomes greater with the increasing of extrusion ratio.